Hospital infection control and behaviour of operating room staff - Lo Giudice, Daniela; Trimarchi, Giuseppe; La Fauci, Vincenza; Squeri, Raffaele; Calimeri, Sebastiano (Central European journal of public health, 2019)
OBJECTIVES: Surgical site infections (SSIs) are a frequent complication of surgical procedures and one of the most common forms of hospital acquired infection (HAI). National/international guidelines and recommendations have been issued for prevention. The objective of this study was to observe the behaviour of healthcare workers engaged in surgical procedures and hence assess compliance with SSI guidelines. METHODS: An observational descriptive study was conducted at a University hospital in southern Italy. A specifically designed form was used to record the actions of the surgical team during randomly selected surgical operations. Observations comprised the use of surgical attire, the frequency of doors opening and the number of staff in the operating room. RESULTS: A total of 308 operating room personnel was observed during 402 surgical procedures: 127 surgeons (41%), 39 anaesthesiologists (13%), 62 nurses (20%) and 80 students in training (26%). 96% of the surgical team wore scrubs, 93% of health workers wore a mask and of these 78% wore it correctly in order to completely cover the nose, mouth and beard (when present), 99% wore a cap (only in 48% was the hair completely covered), 50% of the operators wore gloves, 95% wore shoes dedicated to the operating theater and 23% also wore shoe covers, 56% wore gowns, and 22% had eye protection. Furthermore, the average number of health personnel in the operating theater was 8, the doors remained closed in 261 (65%) surgical operations. CONCLUSION: As the results indicated a low adherence to international guidelines among the personnel, it is suggested that training courses should be provided to increase staff awareness on prevention and management of HAI.
Keywords: směrnice pro lékařskou praxi jako téma; Protective Clothing; Italy; Practice Guidelines as Topic; operating room; operační sály; attitude; surgical site infection; Cross Infection; practice; Surgical Wound Infection; personál nemocniční; international guidelines; Humans; Guideline Adherence; Operating Rooms; Personnel, Hospital; infection control; Itálie; dodržování směrnic; infekce spojené se zdravotní péčí; infekce chirurgické rány; lidé; ochranné oděvy